O papel do professor/educador na atualidade - (:unkn) unknown (Universidade Federal do Pampa, 2024)
This paper explores the challenges faced by teachers in contemporary times, in a world marked by technological evolution and social complexity. The need to reconfigure the role of teachers is highlighted, which must abandon the traditional model and act as a mediator, encouraging autonomy, critical thinking, and interpersonal skills in students, especially those from Generation Z, characterized by being digital natives. Technology is presented as both a challenge and an opportunity, demanding ongoing training for educators to integrate digital tools into pedagogical practices in an innovative and effective way. Education in the 21st century requires a connection between technological innovation and humanization, with the teacher being the link that transforms information into meaningful knowledge. The COVID-19 pandemic, in addition to accelerating the use of digital platforms, reinforced the need to review teaching methods to make them more inclusive, dynamic, and aligned with the realities of today's students. Thus, it is concluded that contemporary education is essentially a practice of constant adaptation and transformation.
Keywords: Educação; Inovações educacionais; Motivação na educação; Educação - Efeito das inovações tecnológicas; Professores – Formação; Professores – Eficiência; Geração Z; Ensino híbrido; Pensamento crítico; Tecnologia educacional; Education; Educational innovations; CNPQ::CIENCIAS HUMANAS